Educação profissional no Brasil: o caso do MedioTec na Escola Técnica de Saúde da Universidade Federal da Paraíba - Medeiros, Luciana Délia Dantas de (2020)
The aims of this research was to analyze the development of the MedioTec Program at the Technical School of Health linked to the Federal University of Paraíba, covering pedagogical and financial aspects, such as a professional education policy. In order to do so, we discuss the understanding of the professionals involved in the MedioTec Program in its short period of existence (July / 2017 to July / 2019), as well as their contributions, difficulties and results presented. The theoretical foundation includes discussions on the evolution of professional education in Brazil, advancing until the development of the program through authors such as Frigotto and Ciavatta (2003), Kuenzer (1997), Macedo (2017), Manfredi (2002), Moura (2007 )), Pires (2005), among others. This research followed a qualitative approach of the case study type, with descriptive characteristics. The procedures used in this research include bibliographic review and document analysis, application of structured questionnaires in the online tool Google Docs - forms, sent through the WhatsApp application in the group formed by graduates and professionals (teachers, mediators, coordinators and multidisciplinary team), responsible for management and execution MedioTec in the researched unit.We concluded, based on the evaluation of the participants in the program, that although the dropout rates were 39.35%, MedioTec had a satisfactory evaluation. Among the positive aspects we highlight the quality of the pedagogical team and the preparation for the job market. As it was UFPB's first experience in offering vacancies in the Program, some difficulties could be identified, such as lack of practical classes and problems in the infrastructure of the support centers and in the transportation of students, but this paper listed some suggestions for improvement for MedioTec editions at UFPB. It is essential to highlight the importance of the Program for the less favored population and the opportunities it brings to the students served.